The Currency According to Quran - Robbani, Shofa; Nailin Nafis (Universitas Nahdlatul Ulama Sunan Giri, 2023)
This study aims to analyze the concept of currency in the Qur?an. It is descriptive research with a qualitative approach. The method used is Maudhu'i, by collecting verses based on similar khitab. Regarding currency, The Qur?an focuses on the nomenclature of the dinar (made of gold) and dirham (made of silver). Throughout the development of Islamic economics and finance, Ulama looked into the concept of currency mainly in its functions as (1) payment instruments, (2) asset measurement value, and (3) economic flow. Due to the characteristics of the dinar and dirham mediums that cannot be applied in the modern monetary system, the currency currently in use is the currency with a medium that is seen as practically viable by the government. The dinar and dirham cannot be used because of (1) the high exchange rate of gold and silver against various goods, (2) the availability of gold and silver declines over time and cannot meet the demand for currency, and (3) gold and silver are not easily portable. Therefore, the characteristics of any agreed medium for issuing currency will remain relevant from the point of view of Islamic economics and finance. The Qur'an only provides dinar or dirham as an example of currency, the main essence of which is that the Qur'an provides provisions on how to manage currency in terms of rights and obligations as well as its relation to religious goals.